A 28GHz low-noise amplifier based on 40nm CMOS - Zeng, Haoyang (Nanyang Technological University, 2023)
This dissertation first introduces the theoretical basis of low-noise amplifiers, which includes active devices in CMOS process, passive devices, common topologies and performance indicators of LNAs. Then the design process of the LNA is introduced, including the selection of bias voltage and active device parameters, the design of on-chip inductor, the design of reducing noise factor and the design of matching network.